Synthetic Triterpenoid RTA dh404 (CDDO-dhTFEA) Ameliorates Acute Pancreatitis. Issue 5 (May 2016) - Robles, Lourdes; Vaziri, Nosratola D.; Li, Shiri; Masuda, Yuichi; Takasu, Chie; Takasu, Mizuki; Vo, Kelly; Farzaneh, Seyed H.; Stamos, Michael J.; Ichii, Hirohito
Abstract : Objectives: Nuclear factor-erythroid-2–related factor (Nrf2) is a ubiquitous transcriptional factor that regulates expression of cellular antioxidant and detoxifying molecules. This study was undertaken to test the hypothesis that administration of the Nrf2 activator (dh404) may attenuate acute pancreatitis. Methods: Rats were treated with dh404 (1 mg/kg) 24 hours before induction of pancreatitis and for 3 days thereafter. Pancreatitis was induced with L-arginine (600 mg/100 g) or cerulein (40 μg/kg). Pancreases were processed for histology and malondialdehyde, whereas serum was analyzed for amylase. Islet extracted human pancreatic tissue from organ donors were used for in vitro studies. The tissues were incubated with dh404 at 0, 250, and 500 nM for 30 minutes, 60 minutes, 12 hours, and 24 hours. Nuclear factor-erythroid-2–related factor nuclear translocation and expression of Nrf2's target genes and inflammatory mediators were determined. Results: The dh404-treated rat pancreases demonstrated significantly less infiltration of inflammatory cells, destruction of acinar architecture, perilobar edema, and necrosis. Serum amylase and pancreatic malondialdehyde in the dh404-treated rats were significantly lower. dh404-treated human pancreatic tissue showed a significantly higher expression of antioxidant enzymes, lower expression of inflammatory mediators, and greater viability against oxidative stress. Conclusion: Administration of dh404 attenuates acute pancreatitis by lowering oxidative stress and reducing proinflammatory mediators.